Common mental disorders and mental health-related quality of life among oral health providers - Carolina Franco de Azevedo; Juliane Kely Fagundes Silva; Higina Kelly Lemos Nogueira; Juliet Rocío Valdelamar Jiménez; Carolina Villa Nova Aguiar; Marta Silva Menezes; Liliane Lins Kusterer (Editorial Ciencias Médicas, 2022)
Introduction: Few studies are available about common mental disorders and mental health-related quality of life among dental healthcare providers. Objective: Describe the common mental disorders and the mental health-related quality of life of members of oral health teams from the primary health care section of the Unified Health System in the Metropolitan Region of Salvador de Bahia, Brazil. Methods: A descriptive cross-sectional study was conducted based on the Symptom reporting questionnaire for the evaluation of common mental disorders, the Health questionnaire about health-related quality of life, and a sociodemographic characterization questionnaire. Results: The study sample was composed of 161 professionals, of whom 59.6% were dentists and 40.4% were dental auxiliaries. Dentists obtained a higher average score in the Symptom reporting questionnaire (p = 0.032), whereas their scores in the mental health domains of the Health questionnaire were lower and significant. Three factors in the Symptom reporting questionnaire exhibited a high negative correlation with the mental health domains of the Health questionnaire. Conclusions: Dentists presented greater symptoms of common mental disorders and mental health-related quality of life deterioration than dental auxiliaries. It is therefore necessary to implement mental health promotion strategies aimed at members of oral health teams.